Legal Dilemma of Fake News Management after ‘Marketplace of Ideas’ - Zhou Yue; Zou Ju (Universitas Muhammadiyah Yogyakarta, 2021)
The ‘marketplace of ideas’ metaphor has gone over a whole century since its birth, and its significance is far-reaching. The protection of freedom of speech in its theory is now manifested as high tolerance of fake news. Germany, France, the United Kingdom, Singapore, Russia, and Malaysia are among the countries attempting to address the worldwide issue of false news. Many nations have included false news regulation into necessary measures such as government management and even legal systems, as can be shown. In the United States, it is difficult to control fake news by legal means, which can only be exerted through extremely limited litigation liability and industry self-discipline. In addition, the transformation of media technology has destroyed the theoretical basis of the ‘marketplace of ideas’. Due to the struggle between the two parties in the United States, fake news has become a ‘floating signifier’ and a discourse tool to attack political opponents. The century-old theory of ‘marketplace of ideas’ is in urgent need of reflection and reconstruction.